Circadian timing and alignment in healthy adults: associations with BMI, body fat, caloric intake and physical activity - Baron, KG (Int J Obes (Lond), 2016)
INTRODUCTION: Disruption of circadian rhythms is one of the proposed mechanisms linking late sleep timing to obesity risk but few studies have evaluated biological markers outside of the laboratory. The goal of this study was to determine the relationship between the timing and alignment of melatonin and sleep onset (phase angle) with BMI, body fat and obesity related behaviors. We hypothesized that circadian alignment (relationship of melatonin to sleep timing) rather than circadian (melatonin) timing would be associated with higher BMI, body fat, dietary intake and lower physical activity. SUBJECTS/METHODS: Adults with sleep duration ≥6.5 hours completed 7 days of wrist actigraphy, food diaries and SenseWear arm band monitoring. Circadian timing, measured by dim light melatonin onset (DLMO) was measured in the clinical research unit. Circadian alignment was calculated as the duration between dim light melatonin onset and average sleep onset time in the prior week (phase angle). Body fat was evaluated using dual-energy absorptiometry (DXA). Data were analyzed using bivariate correlations and multivariable regression analyses controlling for age, sex, sleep duration and evening light exposure. RESULTS: Participants included 97 adults (61 F, age 26.8 ± 7.3 years) with average sleep duration 443.7 (SD= 50.4) minutes. Average phase angle was 2.2 hours (SD= 1.5). Circadian alignment was associated with circadian timing (p<0.001) and sleep duration (p=.005). In multivariable analyses, later circadian timing was associated with lower BMI (p=.04). Among males only, circadian alignment was associated with percent body fat (p=.02) and higher android/gynoid fat ratio (p=0.04). Circadian alignment was associated with caloric intake (p=0.049) carbohydrate intake (p=0.04) and meal frequency (p=0.03) among both males and females. CONCLUSION: Circadian timing and alignment were not associated with increased BMI or body fat, among healthy adults with ≥6.5 hours of sleep, but circadian alignment was associated with dietary intake. There may be sex differences in the relationship between circadian alignment and body fat.